The conceptual evolution of inflation inertia in Brazil - Carvalho, André Roncaglia de (2015)
This work aims to contribute to the wider body of research in history of economics in Brazil by focusing on the conceptual evolution of inflation inertia. Its motivation lies in the conceptual gap that appeared, following disinflation in 1994, between the stabilization debates carried out in the 1980s and the way economists in Brazil began to describe downwardly rigid inflation patterns from the 1990s onwards. More precisely, we explore the \"inertial inflation episode\" as a chapter in a longer tradition of adaptations, to country-specific realities, of theoretical influences coming from the economics profession at the international level, in the late 1970s, when the inertial inflation hypothesis was brought to the fore. Our narrative reveals that this stubborn inflationary phenomenon had been previously dealt with in the debates in Latin America about growth and inflation back in the 1950s and 1960s, where a host of contributions sprung from various traditions, which were gradually synthesized by the saw-tooth model of real wages, also known as Simonsen-Pazos mechanism. We analyze the recurrent opposition between a monetarist- and a heterodox structuralist-type of thinking in their two rounds, in the 1950s and again in the 1980s. The connection between these two opposing schools is operated by the contributions by Mario Henrique Simonsen and the self-declared neo-structuralist economists at PUC-Rio. Based on a careful and detailed analysis of the latter\'s modeling strategies and conclusions, we show that, along the 1980s, these economists gradually shift towards a more ecumenical approach, inviting monetarist elements into their analyses while downplaying the relevance of the inertial component. Finally, when the 1990s came, the rise of a macroeconomic consensus began to conceptualize \"inflation inertia\" as the time delay between a real or monetary shock and the response by price level changes, leaving the concept of \"inflation persistence\" to account for the deviations of inflation away from its equilibrium value, a view that undergirds how most Brazilian economists now understand this phenomenon. We assess how \"inflation inertia\" has been understood in the aftermath of the monetary reform in Brazil in 1994, by analyzing the backstage papers that circulated within the economic team in charge of the Real Plan. We conclude that there are elements of continuity between the two rounds as regards the concept of inertia, but that they are now stripped of their previous dense historical and institutional substance.